2010
DOI: 10.1111/j.1742-7843.2009.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Nano Titanium Dioxide Particles Promote Allergic Sensitization and Lung Inflammation in Mice

Abstract: The purpose of this study was to investigate whether photocatalytic TiO2 nanoparticles have adjuvant effect, when administered in combination with ovalbumin (OVA) in mice. Mice were immunized via intraperitoneal injections of OVA, OVA + TiO2 or OVA + Al(OH)3 and challenged with aerosols of OVA. At the end of the study, serum was analysed for content of OVA-specific IgE, IgG1 and IgG2a antibodies, and the bronchoalveolar lavage fluid (BALF) was analysed for content of inflammatory cells and levels of interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
85
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 31 publications
3
85
3
Order By: Relevance
“…For example, carbon black ultrafine particles, titanium dioxide nanoparticles, carbon nanotubes, and diesel exhaust particles have all been shown to promote allergic sensitization and AAI (5,6,(8)(9)(10)(11)(12)(13)(14). However, there are some important differences between these studies and ours.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…For example, carbon black ultrafine particles, titanium dioxide nanoparticles, carbon nanotubes, and diesel exhaust particles have all been shown to promote allergic sensitization and AAI (5,6,(8)(9)(10)(11)(12)(13)(14). However, there are some important differences between these studies and ours.…”
Section: Discussioncontrasting
confidence: 49%
“…Indeed, ambient pollutant particles and diesel exhaust particles can promote lung inflammation and allergic sensitization (5)(6)(7)(8). Studies have also shown that carbon black nanoparticles (9)(10)(11), titanium dioxide nanoparticles (12), and carbon nanotubes (13,14) can promote allergic sensitization, allergic airway inflammation (AAI), and/or stimulate dendritic cell (DC) and allergen-specific T cells. However, a significant component of these particle adjuvant effects has been attributed to adsorbed toxic chemicals and metallic impurities and the ability to induce oxidative stress (6,7,13,(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Evidence suggests that ambient ultrafine particles (,100 nm) play a disproportionate role in asthma exacerbations compared with fine-sized microparticles (100-2500 nm) (2-5), suggesting that inhaled particle size influences their relative ability to modulate lung function. Similarly, man-made carbon black and titanium dioxide nanoparticles (6)(7)(8) and carbon nanotubes (9,10) all promote allergic sensitization and/or allergic airway inflammation (AAI). However, counterintuitively, we recently made the discovery that preadministration of inert nontoxic polystyrene nanoparticles 50 nm in diameter (PS50G), which do not induce oxidative stress, can inhibit development of AAI by impairing pulmonary dendritic cell (DC) expansion or stimulatory function (11).…”
mentioning
confidence: 99%
“…Immunomodulation have been also observed in in vivo studies (Skocaj et al 2011). Larsen et al (2010) found increased levels of immunoglobulins IgE and IgG1 in the serum and appearance of of eosinophils, neutrophils and lymphocytes in bronchoalveolar lavage fluid after intraperitoneal TiO 2 NPs intake. In the present study, oral administration of carnosine or melatonin showed significant reduced levels of all the studied parameters as they were antioxidants, thus opposed the cytotoxic effects of TiO 2-NPs due to their physicochemical properties can lead to the generation of reactive oxygen species, resulting their accumulation, which in turn, reduce the activities of antioxidant enzymes and antioxidant contents (Warheit et al 2007;Sheng et al 2013).…”
Section: Discussionmentioning
confidence: 83%
“…These studies were in agreement with the present study, which revealed that as regard cardiac functions parameters represented by myoglobin, troponinT and creatine kinase MB isozyme, the results of this study showed significant increase in these parameters, both at low and high doses of TiO2-NPs treated rats. Larsen et al (2010) found that intraperitoneal TiO 2 NPs in mice, lead to liver, kidney and cardiovascular damage indicated by the elevated serum markers of these organs. These elevation were higher in mice treated with NP TiO 2 than those treated with submicron-sized TiO 2 .…”
Section: Discussionmentioning
confidence: 99%